SAPrIm 2.0: a semi-automated protocol for mid-throughput soluble HLA immunopeptidomics - Tanuwidjaya, Erwin; Lim Kam Sian, Terry C. C.; Steele, Joel R.; Goncalves, Gabriel; Woodhouse, Isaac B.; Chang, Janet; Ooi, Joshua D.; Schittenhelm, Ralf B.; Faridi, Pouya (Frontiers in Immunology, 2025)
Human leukocyte antigen (HLA) molecules are pivotal in guiding human adaptive immune responses through their presentation of peptide ligands, collectively known as the immunopeptidome. This process is central to the development of cancer immunotherapies, such as vaccines and T-cell therapies. Profiling the immunopeptidome from plasma and other biofluids has gained increasing traction, as it offers a minimally invasive approach for monitoring disease states and immune responses toward cancer therapy. Here we present the second iteration of SAPrIm, a refined immunopeptidomics tool optimized for soluble HLA analysis. It can process up to 12 samples per batch within a day. In this plasma-focused iteration, we identified approximately 1,200 to 4,000 immunopeptides from 100 µL to 1 mL of plasma, demonstrating high reproducibility across technical replicates, biological replicates, and inter-day analyses. This robust reproducibility highlights the method’s strong potential for reliable relative quantification of immunopeptides in plasma-based studies. This workflow is positioned to advance the field of immunopeptidomics by enabling efficient plasma-based comparative analyses and mid-size cohort studies.